Manajemen Literasi Pesantren dalam Sistem Penjaminan Mutu Berbasis Rekognisi (Studi Kualitatif di Pesantren Sumatera Thawalib Parabek) (Indo-MathEdu Intellectuals Journal, 2026)
Literacy management in pesantren is often not systematically integrated into the educational quality assurance framework. This study aims to analyze the management of students’ literacy within a recognition-based quality assurance system at Pesantren Sumatera Thawalib Parabek. This research employed a qualitative approach using in-depth interviews, observations, and documentation. The informants included pesantren leaders, vice principals, coordinators of the Santri Literacy Forum (Folisa), and students actively involved in literacy activities. The findings reveal that literacy management at Pesantren Sumatera Thawalib Parabek is implemented in a structured manner through planning, implementation, evaluation, and recognition of students’ literacy achievements. The Folisa program functions as an instrument of literacy quality assurance that enhances students’ literacy competencies and provides recognition through publication of students’ works and continuous literacy programs. This study recommends recognition-based literacy management as a best practice for improving the quality of pesantren education.